2016
DOI: 10.1063/1.4946857
|View full text |Cite
|
Sign up to set email alerts
|

Direct assessment of solid–liquid interface noise in ion sensing using a differential method

Abstract: Articles you may be interested in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…For all the pH values, the oxide thickness, t ox , extracted from the impedance modeling is As to the dynamic nature of the system, it is intuitively reasonable, as shown in Finally, it may worth reminding that the real part of the impedance represents the LFN originating from the oxide/electrolyte interface via the definition 4 Re . 16 Our impedance model reveals that the interfacial impedance has a strong correlation to the dynamic H + reactivity at the oxide/electrolyte interface.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…For all the pH values, the oxide thickness, t ox , extracted from the impedance modeling is As to the dynamic nature of the system, it is intuitively reasonable, as shown in Finally, it may worth reminding that the real part of the impedance represents the LFN originating from the oxide/electrolyte interface via the definition 4 Re . 16 Our impedance model reveals that the interfacial impedance has a strong correlation to the dynamic H + reactivity at the oxide/electrolyte interface.…”
Section: Resultsmentioning
confidence: 81%
“…The excellent agreement between the potentiometric LFN and the real part of electrochemical impedance spectrum of solid/liquid systems 16,17 confirms the availability of electrochemical impedance spectroscopy (EIS) as an efficient tool to study the interfacial noise. Of particular prominence with EIS is its capability to effectively probe the dynamic information of the interfacial H + adsorption/desorption.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…As such, low-frequency noise (LFN) is the primary cause responsible for limiting the resolution in sensing applications. Ion sensitive field-effect transistor (ISFET) technology finds a vast variety of applications in chemistry and biomedicine [5][6][7] , and the LFN behavior of an ISFET has received extensive in-depth investigations [2][3][4][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . On one hand, it has been shown that the LFN of the various forms of ISFETs investigated can originate from the solid-state part of the devices, in particular their conducting channel 2,8,[10][11][12]17,20,22 or surrounding dielectric layers 19,21 .…”
mentioning
confidence: 99%
“…On one hand, it has been shown that the LFN of the various forms of ISFETs investigated can originate from the solid-state part of the devices, in particular their conducting channel 2,8,[10][11][12]17,20,22 or surrounding dielectric layers 19,21 . On the other hand, there is evidence showing the ISFET LFN to be a result of the adsorption/desorption events occurring at the sensing surface of the devices 3,4,16,18,23 . Our previous work 16 concludes from experimental viewpoint that the LFN originating from the solid/liquid interface is of thermal nature and its amplitude is comparable with that from the semiconductor/oxide interface.…”
mentioning
confidence: 99%